PERBANDINGAN PENGARUH AIR KELAPA DAN MINUMAN ISOTONIK TERHADAP TINGKAT HIDRASI ATLET CABANG OLAHRAGA BOLA BASKET - Siska Triana Budiman; Hamidie Ronald Daniel Ray (PAIFORI, 2019)
The purpose of this research was to find out the comparison and the effect of coconut water and isotonic drink on hydration status, to reduce anaerobic muscle fatigue and to anticipating blood sugar level increase of basketball athletes. This is quasy experimental research and use a pretest and posttest control group desain. The subject of this research are 18 basketball athletes from UPI's basketball student activity unit with ages 19-21 years old and divided randomly into 3 groups which is 2 treatment groups and control group. The subject givenintervention coconut water, 250 ml of isotonic drink and placebo, it given 30 minutes before the test. The hydration status on basketball athletes is seen from the color of urine and the muscle fatigue measured by using RAST (Running-based Anaerobic Sprint Test) by calculating the value of AF (Anaerobic Fatigue) and blood sugar levels is measured using Autocheck measuring instrument. The result of this research identified that mostly basketball athletes are get dehydration, There is a significant effect on the status of fatigue index according to the type of coconut water and isotonic drink, and also there is a significant difference in the Glicemia level of basketball athletes according to the type of drink.